Fenomenologia do Mecanismo Seesaw Tipo-I - Jesus, Álvaro Santos de (2020)
Neutrinos are elementary particles present on many phenomena in nature, from nuclear physics, such as the beta decay, to cosmology, where neutrinos have an essential role in the evolution of the universe. In the Standard Model of Particle Physics, neutrinos are hypothesized to be massless left-handed particles. However, with the discovery of the neutrino oscillations, it became known that the neutrinos are massive particles, which is direct evidence against the Standard Model. Therefore, there is a necessity for models beyond the Standard Model that can explain how the neutrinos become massive. In this work, we are going to study the Type-I Seesaw Mechanism, which is a model that explains how the neutrinos become massive by adding right-handed neutrinos (RHN) and the hypothesis that neutrinos can be Majorana particles. Even though this is a very simple model to explain the neutrinos masses, it also predicts the existence of several prohibited events, such as lepton flavor violation and lepton number violation processes. To analyze the consequences of the Type-I Seesaw Mechanism, we are going to study processes that have the RHN signature, as well as its phenomenology by using colliders and rare decays, so that we can obtain bounds on the RHN physical properties.